Perceived barriers to accessing mental health services among black and minority ethnic communities: a qualitative study in southeast England. (November 2016) - Memon, Anjum; Taylor, Katie; Mohebati, Lisa M; Sundin, Josefin; Cooper, Max; Scanlon, Tom; de Visser, Richard
Abstract: Background: In most developed countries, substantial disparities exist in access to mental health services for black and minority ethnic populations. We sought to determine perceived barriers to accessing mental health services among people from these backgrounds to inform the development of effective and culturally acceptable services to improve equity in health care. Methods: In this qualitative study in southeast England, 26 adults (13 men, 13 women; aged >18 years) from black and minority ethnic backgrounds were recruited to two focus groups. Participants were identified through the registers of the Black and Minority Ethnic Community Partnership centre and by visits to local community gatherings, and were invited to take part by community development workers. Thematic analysis was conducted to identify key themes about perceived barriers to accessing mental health services. Findings: Participants identified two broad themes that influenced access to mental health services. First, personal and environmental factors included inability to recognise and accept mental health problems, positive impact of social networks, reluctance to discuss psychological distress and seek help among men, cultural identity, negative perception of and social stigma against mental health, and financial factors. Second, factors affecting the relationship between service user and health-care provider included the impact of long waiting times for initial assessment, language barriers, poor communication between service users and providers, inadequate recognition or response to mental health needs, imbalance of power and authority between service users and providers, cultural naivety, insensitivity, and discrimination towards the needs of black and minority ethnic service users, and lack of awareness of different services among service users and providers. Interpretation: People from black and minority ethnic backgrounds require considerable mental health literacy and practical support to raise awareness of mental health conditions and combat stigma. There is a need for improving information about services and access pathways. Health-care providers need relevant training and support in developing effective communication strategies to deliver individually tailored and culturally sensitive care. Improved engagement with people from black and minority ethnic backgrounds in the development and delivery of culturally appropriate mental health services could facilitate better understanding of mental health conditions and improve access. Funding: Public Health Directorate NHS Brighton and Hove, Sussex Partnership NHS Foundation Trust, Black and Minority Ethnic Community Partnership, Brighton and Sussex Medical School.